An Islamic Economic Perspective on the Influence of Perceived Ease of Use and Perceived Usefulness on QRIS Usage Decisions Through Attitude Toward Using as an Intervening Variable: Evidence from MSMEs in Gowa Regency - Azmi Yusriyah Naurah; Jamaluddin Majid; Sudirman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of the perception of ease of use and the perception of usability on the decision to use the Quick Response Code Indonesian Standard (QRIS), with user attitudes as an intervening variable in Micro, Small, and Medium Enterprises (MSMEs) in Gowa Regency in the perspective of Islamic economics. The type of research used is quantitative research with an explanatory approach. Data analysis was carried out using SmartPLS software version 4.11.4 through the Partial Least Squares (PLS) approach to test the validity, reliability, structural model, and research hypothesis. The results of the study show that the perception of ease of use does not have a significant effect on the decision to use QRIS or on user attitudes. On the other hand, the perception of usability has a positive and significant effect on the decision to use QRIS as well as on user attitudes. In addition, user attitudes have a significant effect on the decision to use QRIS. In the mediation analysis, the user's attitude did not mediate the influence of the perception of ease of use on the decision to use QRIS, but succeeded in mediating the influence of the perception of usability on the decision to use QRIS. Overall, the findings of this study show that the decision to use QRIS in MSMEs is more driven by the perception of benefits than the perception of ease of use. From an Islamic economic perspective, these results are in line with the principles of maqasid al-shariah, especially maslahah (public benefit) and hifz al-mal (protection of property), where the adoption of technology is expected to provide real benefits, increase efficiency, and ensure safe and transparent financial transactions.